1957
DOI: 10.1002/bjs.18004418618
|View full text |Cite
|
Sign up to set email alerts
|

The effect of endocrine ablation on the healing of incised wounds in aponeurosis

Abstract: I N a previous study (Douglas, 1952) it was observed that the healing of incised wounds in the lumbodorsal aponeurosis of rabbits followed a regular pattern in which two features were prominent :-exponential in form and in two independent sets of data was very similar.It was originally intended to have 20 animals in each group, but because of the high mortality of hypophysectomy and of adrenalectomy, we had to be content with 15 and 11 animals in these groups Hypophysectomy was carried out by the parapharyngea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1959
1959
1960
1960

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In contrast to the work outlined by Harvey (1949) (see above), where the strength of wounded tissue eventually exceeded that of the normal, Douglas (1952) studied the healing of incised wounds in the lumbo-dorsal aponeurosis of rabbits, and found that even after one year the original strength of the tissue had not been regained. The repair was not influenced by the pituitary, adrenal or thyroid glands (Douglas, 1957). Thorngate & Ferguson (1958) noted that similar wounds in the rabbit healed with greater strength when under tension.…”
Section: ( I ) Epithelial Reactionsmentioning
confidence: 93%
“…In contrast to the work outlined by Harvey (1949) (see above), where the strength of wounded tissue eventually exceeded that of the normal, Douglas (1952) studied the healing of incised wounds in the lumbo-dorsal aponeurosis of rabbits, and found that even after one year the original strength of the tissue had not been regained. The repair was not influenced by the pituitary, adrenal or thyroid glands (Douglas, 1957). Thorngate & Ferguson (1958) noted that similar wounds in the rabbit healed with greater strength when under tension.…”
Section: ( I ) Epithelial Reactionsmentioning
confidence: 93%